The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/19443994.2014.884475
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic degradation of azo dyes using three macrophyte species:Arundo donax,Typha angustifoliaandPhragmites australis

Abstract: A B S T R A C TThe aim of this study was to investigate the potential role of three macrophyte species (Arundo donax, Typha angustifolia and Phragmites australis) for degradation of azo dyes. Activities of peroxidases enzymes involved in plant protection against stress were tested for dye decolourization. In order to conduct the enzyme activity assay, the fresh extract was obtained from crude extracts of leaves. The oxidation capability of peroxidase (POD) on direct azo dyes (amaranth and amido black) was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…De'Souza et al (2007) reported HRP decolorization efficiency to the tune of 59%, 94% and 52% on dyes remazol turquoise blue G, lanaset blue 2R and textile effluents, respectively. Haddaji et al (2015) studied the potential role of enzyme peroxidases found in three macrophytic plants (Arundo donax, Typha angustifolia and Phragmites australis) for the degradation of direct azo dyes amaranth and amido black and found that it is an effective degradation methodology.…”
Section: Decolorization and Degradation Of Azo Dyes By Peroxidasesmentioning
confidence: 99%
“…De'Souza et al (2007) reported HRP decolorization efficiency to the tune of 59%, 94% and 52% on dyes remazol turquoise blue G, lanaset blue 2R and textile effluents, respectively. Haddaji et al (2015) studied the potential role of enzyme peroxidases found in three macrophytic plants (Arundo donax, Typha angustifolia and Phragmites australis) for the degradation of direct azo dyes amaranth and amido black and found that it is an effective degradation methodology.…”
Section: Decolorization and Degradation Of Azo Dyes By Peroxidasesmentioning
confidence: 99%
“…This result is promising since studies that used peroxidases have reported a nity with other dyes. For example, peroxidase extracted from industrial soybean residues was e cient in degrading blue dye after 3.3 hours of reaction (70% degradation) 28 , and peroxidase from macrophytes performed well in the degradation of direct azo dyes, such as amaranth and black starch (93% and 87%, respectively, after 120 hours of reaction) 29 . Also, for the blue dye, two peroxidase sources (Ipomea palmata and Saccharum spontaneum) showed removals of 15% and 70%, respectively, after 1 to 2 hours of treatment, indicating different speci cities of plant peroxidase to the same dye 30 .…”
Section: Relationship Between Enzymatic Activity and Discoloration Potentialmentioning
confidence: 99%
“…T. orientalis is also proven to contribute towards reduction of heavy metals and pesticides level in water bodies [75]. T. angustifolia cause phytoremediation of chromium and enzymatic degradation of azo dye [76,77]. In the Ashi River Basin (India), its pollutant removal property has been studied [78].…”
Section: Phytoremediation and Bioenergy Sourcementioning
confidence: 99%
“…A study on the allelochemicals produced by two species of this genus indicated that T. angustifolia is invasive, while T. latifolia is not invasive in North America [10]. T. angustifolia is also shown to exert allelopathic effects on phytoplanktons [76].…”
Section: Allelopathic Effectmentioning
confidence: 99%